Question Number 186867 by Mingma last updated on 11/Feb/23 | ||
![]() | ||
Answered by aba last updated on 11/Feb/23 | ||
![]() | ||
$${x}=−\mathrm{5} \\ $$$$\left(\mathrm{1}−\frac{\mathrm{1}}{\mathrm{5}}\right)^{−\mathrm{4}} =\left(\frac{\mathrm{5}}{\mathrm{4}}\right)^{\mathrm{4}} =\left(\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}}\right)^{\mathrm{4}} \\ $$ | ||
Commented by Mingma last updated on 11/Feb/23 | ||
Good! | ||
Answered by aba last updated on 11/Feb/23 | ||
![]() | ||
$$\left(\mathrm{1}+\frac{\mathrm{1}}{{x}}\right)^{{x}+\mathrm{1}} =\left(\mathrm{1}+\frac{\mathrm{1}}{\mathrm{4}}\right)^{\mathrm{4}} \Rightarrow\:\left(\mathrm{1}+\frac{\mathrm{1}}{{x}}\right)^{{x}+\mathrm{1}} =\left(\mathrm{1}−\frac{\mathrm{1}}{\mathrm{5}}\right)^{−\mathrm{5}+\mathrm{1}} \\ $$$$\Rightarrow{x}=−\mathrm{5}\: \\ $$ | ||
Commented by Mingma last updated on 11/Feb/23 | ||
Good! | ||